Superprodução de ramnolipídeo em Saccharomyces cerevisiae: Construção de vetores de expressão - Campos, Rayane Luzia Viegas Campos (2015)
Biosurfactants are metabolites that contain both hydrophobic and hydrophilic domains and are produced by various microorganisms. Due to its characteristics such molecules localize preferable in the interface of polar and non-polar solvents. Biosurfactants are widely used in pharmaceutic, cosmetic, food and agriculture industries. Moreover, they are considered advantageous when compared to chemical ones because they are biodegradable and non-toxic. Currently one of the best known biosurfactant is the rhamnolipids. However, their utilization in large scale are still not possible due to its high production costs. Rhamnolipids are produced mainly by Pseudomonas aeruginosa and are composed by one or two molecules of L-rhamnose attached to a fatty acid molecule. This study aimed the construction of yeast expression vectors that will be used to construct a recombinant strain of Saccharomyces cerevisiae efficient in the production of L-rhamnose and mono-rhamnolipid using sucrose as substrate. For the construction of these vectors, six different genes, responsible for encoding both L-rhamnose and mono-ramnolipideos biosynthetic pathways enzymes described in P. aeruginosa (rmlA, rmlB, rmlC, rmlD, rhlA and rhlB), and one gene, responsible for the synthesis of a substrate break enzyme, described in Pelomonas sacchraphyla (sucrose phosphorylase) were utilized. The genetic engineering proposed in this study is innovative, and has never been done before. The production of rhamnolipid in large-scale at low costs will be highly beneficial for the development of national technologies for production of high value-added chemical.